ULTRASTRUCTURAL FEATURE OF KOI HERPESVIRUS (KHV) INFECTED CULTURED KOI FIN (KF-1) CELLS - Ketut Mahardika; Masahiro Yasuda (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
Koi herpesvirus (KHV), may cause significant morbidity and mortality in common carp (Cyprinus carpio). In the present study, an electron microscopic (EM) was performed on KHV-infected cultured koi fin (KF-1) to document the ultrastructure of the lesions. Viral particles were firstly evident in the nucleus. These viral particles observed as immature capsids and nucleocapsids. Many non-enveloped nucleocapsids have moved from the nucleus into the cell cytoplasm. The formation of subviral particles and virions, which comprised, in turn, an electron dense core, capsids with a hexagonal outline, the tegument was evident in the cytoplasm. And then, the virions with the enveloped tegument budded through the intracytoplasmic membrane. Based on EM results, the definitive pathological change was similar as those in the Family Herpesviridae.